Investigation of a single-layer EBC deposited on SiC/SiC CMCs: Processing and corrosion behaviour in high-temperature steam - Al Nasiri, N.; Patra, N.; Pezoldt, Marc; Colas, J.; Lee, W. E. (Journal of the European Ceramic Society, 2019)
Two rare earth monosilicates (Yb2SiO5, and Lu2SiO5) were deposited using a low-cost coating application method to produce a single-layer coating. RE-oxides slurries were dip coated on oxidised CMC samples and subsequently heat treated at high temperature to ensure reaction between SiO2 and RE-oxides to form the RE-monosilicate. A single, continuous, homogeneous thick coating of 25 pm was obtained. X-ray diffraction (XRD) confirmed formation of, RE-monosilicates in Yb and Lu silicate systems. Coated samples were exposed to 90% H2O static steam environment at 1350 degrees C for 25, 50, 100, and 150 h. Scanning Electron Microscopy (SEM) indicated that both coatings adhered strongly to the substrate. Coating thickness reduced from 22 mu m to 11 mu m for Yb-coating and 13 to 4 pm for Lu-coating with increasing corrosion time from 25 to 150 h, however there was no significant attack of the CMC for all steam exposure times.
CRIS-Team WoS Importer:2019-05-03